Enhancing Reading Skills: Manga Readers' Perception of English Translations - Nor, Hidayah; rahimah, annisa aulya; asfihana, raida (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
This research is examining the perceptions of manga readers towards English-translated manga and its impact on their reading skills. It evaluates both micro and macro aspects of reading skills enhancement. Employing a convergent mixed methods approach, data was collected in two phases: qualitative interviews with 15 active manga readers and quantitative questionnaires with the same participants. Results indicate a positive perception among manga readers towards English-translated manga, facilitating self-directed learning and enhancing English reading skills. Improvement spans across various reading skills, including linguistic aspects such as grammatical form and word meaning, and macro skills like identifying main ideas and extracting general information. The study, conducted at the English Education Department of Antasari State Islamic University Banjarmasin, suggests that English-translated manga effectively attract readers and motivate them to engage with English materials. Recommendations for future research include exploring similar media formats like webtoons or comics, investigating other reading skills such as writing, and conducting further tests to assess the extent of reading skill improvement among manga readers.